Analysis of Single Cell RNA-seq Data Revealed Interferon Gamma Signaling Alteration in Severe COVID patients - Elbaz, Ahmed (AUC Knowledge Fountain, 2021)
Background: SARS-COV2 virus detected in December 2019, and was considered a pandemic in March 2020 by the WHO. Symptoms range from asymptomatic to life threatening ones. Studying cell-cell interactions in patients' blood samples may lead to novel diagnosis and treatment approaches. Aim: This study aims to analyze single-cell RNA sequencing data to identify differences in cell-cell communications between healthy and COVID patients and differentially expressed T-cells genes that contributed to immune system antiviral activity. Materials and methods: Single-Cell RNA sequencing data from seven COVID patients and five healthy individuals were collected from (GEO accession GSE155673). Cell types were identified and cell-cell interactions were inferred for each condition (healthy, moderate and severe COVID patients). Additionally, T cells differentially expressed genes between the three conditions were identified and pathways enrichment were performed. Results: Eight cell types were identified. Percentage of T cells decreased from 32.76% in healthy individuals to 16% in severe COVID cases. Cell-Cell interactions analysis revealed significant alterations among healthy, moderate, and severe conditions such as reduction of overall incoming signaling in T cells of severe cases. Additionally, SN signaling pathway was identified only in COVID cases, which in turn was found to be in IFN-γ reduction in distinct cell types. Pathways enrichment analysis identified IFN-γ signaling to be upregulated in moderate cases, and to be downregulated in severe ones. Protein interacting with IFN-γ also shows downregulation such as IRF1. However, the negative regulator of IFN-γ -SOCS3- was upregulated in COVID patients T cells. Conclusion: Cell-cell interactions alteration in COVID patients might have resulted in eliciting improper immune response. Not only, did T cells percentage decreased in severe COVID cases, but also T cells overall incoming signaling was decreased. Additionally, cell-cell interaction alteration might have played a significant role in suppressing antiviral response through IFN-γ reduction which might contribute to the observed severity of COVID cases.